Suspending DNA Origami Between Four Gold Nanodots. Issue 2 (17th November 2015) - Morales, Piero; Wang, Liqian; Krissanaprasit, Abhichart; Dalmastri, Claudia; Caruso, Mario; De Stefano, Mattia; Mosiello, Lucia; Rapone, Bruno; Rinaldi, Antonio; Vespucci, Stefano; Vinther, Jesper; Retterer, Scott; et al.
Abstract : Rectangular DNA origami functionalized with thiols in each of the four corners immobilizes by self‐assembly between lithographically patterned gold nanodots on a silicon oxide surface.